2023
DOI: 10.1007/s11845-023-03300-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in geriatric psychiatry—retrospective cohort study of a 6-year period

Abstract: Objective To investigate the frequency and characteristics of adverse drug reactions (ADRs) that occurred on the gerontopsychiatric ward of Hannover Medical School over a 6-year period. Design Retrospective monocentric cohort study. Results Six hundred thirty-four patient cases (mean age 76.6 ± 7.1 years; 67.2% female) were analysed. In total, 92 ADRs in 56 patient cases were registered in the study population. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…197 Another example of the increased risk from polypharmacy for medical and psychiatric conditions in the finding that SSRIs and SNRIs can promote electrolyte disturbances such as hyponatremia when used alongside thiazide diuretics. 197 Conversely, efforts to review and decrease prescriptions can reduce hospitalization and death in nursing home patients 208,209 and reduced mortality in ambulatory settings. 210 Previous studies have indicated the importance of working with an interdisciplinary team including pharmacists, nurses, and other professionals.…”
Section: Implications Of Polypharmacy For Multimorbiditymentioning
confidence: 99%
See 4 more Smart Citations
“…197 Another example of the increased risk from polypharmacy for medical and psychiatric conditions in the finding that SSRIs and SNRIs can promote electrolyte disturbances such as hyponatremia when used alongside thiazide diuretics. 197 Conversely, efforts to review and decrease prescriptions can reduce hospitalization and death in nursing home patients 208,209 and reduced mortality in ambulatory settings. 210 Previous studies have indicated the importance of working with an interdisciplinary team including pharmacists, nurses, and other professionals.…”
Section: Implications Of Polypharmacy For Multimorbiditymentioning
confidence: 99%
“…197 In linking these agents with the most frequent adverse drug reactions, the authors noted that antipsychotic medications are a known contributor to extrapyramidal side effects and join tricyclic antidepressants as the two main psychotropic agents known to influence blood pressure and heart rate -with an increased risk of the latter effect when they are taken in combination with cardiovascular agents such as antihypertensives and various diuretics. 197 Another example of the increased risk from polypharmacy for medical and psychiatric conditions in the finding that SSRIs and SNRIs can promote electrolyte disturbances such as hyponatremia when used alongside thiazide diuretics. 197 Conversely, efforts to review and decrease prescriptions can reduce hospitalization and death in nursing home patients 208,209 and reduced mortality in ambulatory settings.…”
Section: Implications Of Polypharmacy For Multimorbiditymentioning
confidence: 99%
See 3 more Smart Citations